Actual validation of energy simulation and investigation of energy management strategies (Case Study: An office building in Semnan, Iran). (September 2018) - Fathalian, Afshin; Kargarsharifabad, Hadi
Abstract: Due to the wide range of parameters effect in energy consumption within a building, it is not possible to make a proper decision about the impact of different energy efficiency strategies without simulation tools. In this study, the annual energy consumption of an office building in Semnan, Iran is simulated using DesignBuilder software. The validation of simulation results is down by monthly electricity and natural gas energy consumption billing records with the highest simulation error of about 1.6%. Three strategies are proposed to management the energy consumption, e.g. the replacement of single-glazed windows with low-emission double-glazed window, installation of a thermal insulation sheet on the external wall of the building and use of horizontal shadings on the outside and removal of the internal shades. The simulation results show that these strategies lead to 14%, 18% and 13% reduction in energy consumption, respectively. In order to revalidate the simulation, the strategy of replacing the existing windows with low-emission double-glazed is adopted and the actual energy consumption of the building is compared with the simulated value after one year, indicating a good agreement at this stage.